Sediment to water column fluxes of dissolved inorganic carbon and total alkalinity in Red Sea mangroves - Vincent Saderne; Marco Fusi; Timothy Thomson; Aislinn F Dunne; Fatima Mahmud; Florian Roth; Susana Carvalho; Carlos Manuel Duarte (PANGAEA, 2020)
The data describes fluxes of dissolved inorganic carbon (DIC) and total alkalinity (TA) in mmol m?^2 h?^1 measured in a red sea mangrove and adjacent coral lagoon (negatives fluxes are uptake of TA or DIC by the sediment). The incubations were conducted in a mono-specific Avicennia marina mangrove forest of the central Red Sea (22° 20 extquotesingle 23" N, 39° 05 extquotesingle 22" E). The incubations were conducted during the last 2 hours of the rising tide, around solar noon and at night within the same day. The Incubations were conducted from April 2018 to May 2019. In April/May 2018, day and night incubations were done 15 days apart.